LONG TERM EFFECTS OF DIETARY FAT/OILS ON SERUM AND TISSUE CHOLESTEROL LEVEL IN ALBINO RATS - Sohato, Mir Muhammad; Rajper, Ghulam Murtaza; Memon, Abdul Qayoom; Menton, Gulshan; Tayab, Muhammed; Khan, Haleemuddin (Journal of Ayub Medical College Abbottabad, 1999)
The study was carried on 60 albino rats of 8 weeks' age. These rats were divided into five (n= 12) each groups. Low Fat (LF) (5%) diet group and High Fat (HF) (20%) diet groups i.e. Olive Oil (00), Corn Oil (CO) & Butter Fat (BF) group respectively. I IF diet was given for 12 weeks and then the diets were admixed with cholesterol and Propylthiouracil fat for the next 20 weeks. LF diet group were divided into two groups after 12 weeks. Once received LF diet and the other received HF diet with cholesterol and PTH. In our study the serum cholesterol level increased in HF (20%) diet group. The LF (5%) diet, CO (20%), OO (20%) decreased the serum cholesterol level before the supplementation of atherogenic elements but it slightly increased the serum cholesterol level after atherogenic supplementation. On the other end BF diet increased the serum cholesterol level before and after atherogenic supplementation. However, the tissue cholesterol level increased 3 fold in all type of tissues in BF diet group as compared to other diet groups. Least rise in tissue cholesterol level were seen in CO diet group.